England in the thirteenth century - Harding, Alan (Cambridge University Press, 1993)
This is a comprehensive account of politics, government and society in thirteenth-century England. Three episodes stand out: the revolt of the barons against King John in 1215, the protest against the misgovernment of Henry III which began in 1258, and the resistance to the demands of Edward I on the resources of the land which came to a head in 1297. Professor Harding places these political events in the context of social and economic change, in order to provide a rounded account of the century. The introduction demonstrates the constitutional importance given by past historians to the period which saw the framing of the Magna Carta and the beginnings of Parliament and statute law. The central chapters describe the developing social structure of peasants, townsmen and professional people, knights, clergy and lay magnates. The book finally sees the politics of the century in terms of royal ambitions to dominate Britain and to play a leading role in Europe
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1200-1300; Geschichte; Großbritannien; Great Britain / History / 13th century; England / Civilization / 1066-1485; England